Autoimmune manifestation in splenic atrophy presented with toxic shock syndrome: a case report - Liang, Song Zhi; Han, Poh Yeh; Singam, Gaithridevi V; Yong, Tan Sue; Thomson, Koo; Adlihafizi Ab Aziz; Lim Shiao Hui; Kuai Chen Chuan; Ong Lay Sim; Lim Chew Har (Published by Universitas Gadjah Mada, 2024)
Splenic atrophy is an uncommon diagnosis, associated with autoimmune gastrointestinal disorders and other well-characterized connective tissue diseases. We would like to contribute a case report to support the association evidence of the real-world data. To our best knowledge, there is no similar case of splenic atrophy with the presentation of streptococcal toxic shock syndrome reported. Our patient was initially detected with atrophic spleen via CT scan and subsequently diagnosed with systemic sclerosis. Hyposplenism should be suspected in patients with adult-onset infections caused by encapsulated bacteria, especially if autoantibodies are present. Our patient received her pneumococcal vaccination before discharge and was followed in the clinic for further vaccination education and health check-up. Learning points: 1) Acquired splenic atrophy is a rare condition that may be suspected from persistent isolated thrombocytosis after the resolution of sepsis and Howell-Jolly bodies from peripheral blood film; 2) The pathophysiological mechanism of splenic atrophy in the context of autoimmune disorders remains unknown; 3) A high index of suspicion towards the evaluation of splenic function is required if a patient presented with community-acquired encapsulated organism bacteraemia; 4) Vaccination against encapsulated bacterial agents should be performed in patients with hyposplenism.